The effect of product market competition and growth opportunity on the relationship between ownership concentration and abnormal returns - Rahim Bonabi Ghadim; Shabnam Rajaee; Davod Mostafazadeh (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: Ownership concentration can lead to the agency problem between dominant shareholders and minority shareholders (ownership conflict) and the existence of product market competition as a substitute for strong corporate governance and the existence of growth opportunities that can affect the future performance of the company due to information uncertainty, the intensity of management oversight and thus the efficiency of ownership concentration can be affected. The purpose of this study is to investigate the effect of product market competition and growth opportunities on the relationship between ownership concentration and abnormal returns.Methodology: This research is applied in terms of purpose and causal (post-event) in terms of method. The statistical population of the study is the companies listed on the Tehran Stock Exchange and using systematic sampling method, 130 companies were selected as a research sample for a period of 9 years between 2015 and 2023.Findings: The results of testing the research hypotheses with multiple regression showed that ownership concentration has a negative effect on abnormal returns and product market competition and growth opportunity have a significant negative and positive effect on the relationship between ownership concentration and abnormal return, respectively.Originality/Value: The concentration of ownership leads to the problem of representation between dominant shareholders and minority shareholders (conflict of ownership) and the existence of product market competition as a substitute for strong corporate management and also the existence of growth opportunities that affect the company's future performance due to information uncertainty. It affects management supervision and as a result the efficiency of ownership concentration.